Environmental Performance, Company Size, Profitability, And Carbon Emission Disclosure - Masiyah Kholmi; Attika Dewi Shaqinnah Karsono; Dhaniel Syam (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This study aims to examine the effect of environmental performance, company size, profitability on disclosure of carbon emissions in non-service companies listed on the Indonesia Stock Exchange (IDX). The population of this study used non-service companies listed on the Indonesia Stock Exchange (IDX) in 2017. The research sample was 34 companies selected through the purposive sampling method. The data collection technique using documentation method. Data analysis techniques using multiple regression analysis with statistical tools used are SPSS V.24. The results showed that the company's environmental performance did not influence the company to conduct carbon emission disclosure. by obtaining a PROPER rating, it does not guarantee the company will disclose carbon emissions properly. While company size and profitability, have no effect on carbon emission disclosure, because companies still choose to make other disclosures that can increase their legitimacy in the eyes of the public. Companies consider carbon emission disclosure as not yet able to add value to companies and the nature of emissions disclosures carbon which is still in the form of voluntary disclosure. This research contributes to disclosure of carbon emissions from company activities in the annual report and the company can prevent and reduce carbon emissionsc.